SISTEM KOREFERENSIAL KLAUSA SUBORDINATIF BAHASA INDONESIA - Netra, I Made; Pita, Petrus; Mandra, I Wayan; Subiyanto, Paulus (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2008)
Abstract This article focuses on the coreferential systems of the Indonesian subordinative clauses. The specific aims are to analyze the Indonesian language typology morphosyntactically, the morphological alteration that brings about the argument structures, and the coreferential behaviour. The data were taken from the Indonesian complex sentences taking the forms of the combination of: 1) intransitive clause and intransitive clause, 2) intransitive clause and transitive clause, 3) transitive clause and intransitive clause, and 4) transitive clause and transitive clause. The theory employed is the theory of typology proposed by Comrie (1988) modified by Artawa (2004). The result of the analysis showed that the Indonesian language does not belong to such language typologies as accusative, active, passive, ergarive, and antipassive; the morphological alteration of the verb can result in the argument structures of the clause taking the forms and marked with zero and personal pronoun; and the basic coreferential system of the Indonesian language may be in the forms of S = P in which A is different, and S = A in which P is different, while the derived systems, which are based upon the combination of clauses, are as follows: (1) S = S, (2) S = P, (3) S = A, (4) A = S, (5) P = S, (6) A = A, (7) A = P, and (8) P = A.